Educator from the Perspective Quran - Wilrahmi Izati; Afifah Febriani; Gifa Oktavia; Syafrul Nalus (Nida Al-Qur'an: Jurnal Pengkajian Islam, 2024)
Islam has a very high regard for teachers. The position of teachers is a level below that of Prophets and Apostles. Some of their hadith histories have received nicknames warâtsatu al-anbiyâ (heirs of the prophets), and likened their superiority compared to others, like the full moon in the midst of the stars. In fact, the high position of teachers in Islam is a realization of Islamic teachings themselves. Islam glorifies knowledge, knowledge is obtained from learning and teaching. Because Islam is a religion, the view of teachers, the position of teachers, cannot be separated from heavenly values. While the Quran mentions at least four classifications of educators, they basically have "similarities" in coaching students according to their respective objectives and lead to the enforcement of the sentence of Allah. This research uses a qualitative method with a thematic analysis approach. Based on an investigation of the verses of the Quran which contain vocabulary as an educator, it can be concluded that the vocabulary of ahl al-zikr, ‘ulama, al-muwaiz al-waizin, uli al-nuha, mu’allim, al-muzakki, murabbi, al-rasikhuna fi al-‘ilm, ulul albab and ulu al-absar actually have meanings that are interconnected or intertwined. As shown above, there are some vocabulary words that have almost the same meaning, but there are also vocabulary words with special emphasis. Broadly speaking, the verses that contain a variety of vocabulary confirm that an educator needs various qualities and with those qualities he works to carry out the mission of educating.